Conventional and Unconventional Brand Protection in IndonesiaConventional and Unconventional Brand Protection in Indonesia - Monica Olivia (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to determine the legal protection of conventional and unconventional brand registration in Indonesia. This research is normative research using legal materials to solve facts or legal issues and to obtain legal materials and analyze them through literature studies (legislation and literature). This study used 2 (two) problem approaches, namely the statutory approach and the conceptual approach. The findings revealed that conventional brand is limited to signs in the form of pictures, names, words, letters, numbers, color arrangements, or combinations of elements that have distinguishing features and are used in trading activities of goods or services. However, for a product/service that does not qualify in terms of a conventional brand, it is generally known as a unconventional brand. The regulation of non-conventional marks in Indonesia is outlined in Article 1 (1) of Law 20/2016. However, this regulation only covers marks in the form of three dimensions, sound, and holograms. Indonesia currently only regulates unconventional marks that fall under these categories. This poses a potential issue as the market is witnessing a growing variety of marks, and the regulation of position marks has not yet been addressed in Indonesia.